Pengaruh Perbandingan Puree Belimbing Manis (Averrhoa carambola L.) Dan Dami Nangka (Artocarpus heterophyllus L.) Terhadap Karakteristik Fruit Leather - ., Ita; Ari Yusasrini, Ni Luh; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i02.p02, 2021)
This study aims to determine the effect of the comparison of sweet star fruit puree and jackfruit straw on the characteristics of fruit leather and find  the comparison of sweet star fruit puree and jackfruit straw to produce fruit leather with the best characteristics. This research used Completely Randomized Design (CRD) with a comparison treatment of sweet star fruit puree and jackfruit straw as treatments consisting of 5 levels, namely comparison of 95% sweet star fruit puree : 5% jackfruit straw (P1), 90% sweet star fruit puree : 10% jackfruit straw (P2), 85% sweet star fruit puree : 15% jackfruit straw (P3), 80% sweet star fruit puree : 20% jackfruit straw (P4), 75% sweet star fruit puree : 25% jackfruit straw (P5). Each treatment was repeated 3 times resulting in 15 experimental units. The parameters observed included water content, ash content, crude fiber content, pectin content, vitamin C content, total sugar, and sensory properties including color, texture, flavor, taste and overall acceptance. The data generated is then analyzed with Analysis of Variance method and if the treatment affects the observed parameters, followed by the Duncan Multiple Range Test (DMRT). The results showed that the comparison of sweet star fruit puree and jackfruit straw affected the water content, ash content, crude fiber content, pectin content, vitamin C content, color, texture and flavor test. Comparison of 75% sweet star fruit puree : 25% jackfruit straw produce the best characteristic fruit leather with water content characteristics of 10,85%, ash content of 0,86%, crude fiber content of 3,42%, pectin content of 3,03%, vitamin C content 3,68 mg AAE / g, total sugar 82,37%, brownish yellow color and preferred, slightly clay and neutral texture, taste, flavor and overall acceptance are preferred.